RELATIONSHIP OF AMBIENCE OF THE SPORT-LEISURE PRATICER AT THE MIÉCIMO DA SILVA SPORTS CENTER : APPROACHING THE ANALYSIS OF SPEECH (PÊCHEUX) (Fiep Bulletin - online, 2015)
This study aims to identify, through the Analysis of Speech, the sport-leisure practice's opinion related to the practice of certain sport and to the place of practicing (ambience). 6  volleyball apprentices and 15 swimming apprentices were interviewed. Both groups accomplished their sports modality as leisure at Miécimo da  Silva Sports Center  (MSSC), in Campo Grande,  west of  Rio de Janeiro. The study is justified by the increasing search for moments of leisure in the area. Its social relevance is related to discoveries of the apprentices' thought about the relationship to the use of this sporting space. Limiting factors were imposed to the apprentice's participation in the research, such as: Accomplishment of the sport-leisure practice  (at least three times a week) and  age group between 20 and 40 years (grownups). Regarding the results, it can be said that the analysis accomplished through the speech, the outfit, and the interaction among players, indicates a  valorization of  leisure practice, of the natural atmosphere (contemplating the nature) and of freedom. It was reported  that the desires that make the practice of sport-leisure are associated to another social activity - meeting friends, drinking beer. Finally, the practice of  swimming-leisure was less motivating for social interactions, when compared to the volleyball-leisure practice.
Keywords: SPORT-LEISURE; Sports SPACE; ANALYSIS OF SPEECH.